Determination of Optimal Batch Size of Deep Learning Models with Time Series Data - Hwang, Jae Seong; Lee, Sang Soo; Gil, Jeong Won; Lee, Choul Ki (Sustainability (Switzerland), 2024)
This paper presents a new method to determine the optimal batch size for applying deep learning models with time series data. A set of batch sizes is determined by considering the length of the repetition pattern of the data using the Fast Fourier Transform (FFT). A comparative analysis is conducted to identify the impact of varying batch sizes on prediction errors for the three deep learning models. The results show that the RNN model has the optimal batch size that produces the minimum prediction error. In the DNN and CNN models, the optimal batch size is not correlated with the repetition pattern of time series data. Therefore, it is not recommended to apply CNN and DNN models of time series data. However, if used, a small batch size can be selected to reduce training time. In addition, the range of prediction error according to batch size is significantly larger for RNN models compared to DNN and CNN models.
Keywords: batch size; deep learning; FFT; hyper-parameter; time series data